Pengembangan Masyarakat Program Holistik Pembinaan dan Pengembangan Desa (PHP2D) pada Kelompok Rukuntani di Desa Bantarsari: Community Development Program for Holistic Development and Village Development (PHP2D) for the Rukuntani Group in Bantarsari Village - Qorirah Iftinani; Situmeang, Widya Hasian; Leonard Dharmawan (Jurnal Sosial Terapan, 2023)
One of the community development methods is Participatory Rural Appraisal (PRA) with various techniques that strive for community development to be carried out according to the needs of the community. The Participatory Rural Appraisal (PRA) method uses the basic concept of community involvement in all activities by emphasizing community participation. The Ministry of Education of the Republic of Indonesia encourages educational institutions to carry out Free Learning Campus Merdeka (MBKM) activities, as a learning platform for students as well as a space for implementing the tri dharma of higher education, especially in the context of community service. This paper intends to analyze the implementation of the Independent Campus Learning (MBKM) activities through the Holistic Village Development and Development Program (PHP2D) in Bantarsari Village. The community development activities carried out by PHP2D consisted of several stages: identification of potentials and problems, formulation of action plans, follow-up (surveys, outreach, preparation of facilities and infrastructure, training on honey bee cultivation), evaluation and follow-up of the program at the Rukun Tani Group. Observations on the community development program conducted by PHP2D show that this activity has not been fully implemented in the spirit of community development. The activities carried out tend to be top down and are in the form of knowledge transfer without any organizing of community development subjects. The activities carried out showed that there was no direct participation by the Rukun Tani group so that the collectivity of the Rukun Tani groups did not appear for the Bantarsari Village PHP2D program and the program's sustainability was not implemented. ABSTRAK Salah satu metode pengembangan masyarakat adalah Participatory Rural Appraisal (PRA) dengan berbagai teknik yang mengupayakan agar pengembangan masyarakat yang dilakukan sesuai dengan kebutuhan komunitas. Metode Participatory Rural Appraisal (PRA) menggunakan konsep dasar keterlibatan masyarakat pada keseluruhan kegiatan dengan memberikan tekanan pada partisipasi oleh masyarakat. Kementerian Pendidikan Republik Indonesia mendorong institusi pendidikan melaksanakan kegiatan Merdeka Belajar Kampus Merdeka (MBKM), sebagai wadah pembelajaran bagi mahasiswa sekaligus ruang bagi pelaksanaan tri dharma perguruan tinggi, terutama dalam konteks pengabdian masyarakat. Tulisan ini bermaksud menganalisis pelaksanaan kegiatan Merdeka Belajar Kampus Merdeka (MBKM) melalui Program Holistik Pembinaan dan Pengembangan Desa (PHP2D) di Desa Bantarsari. Kegiatan pengembangan masyarakat yang dilakukan oleh PHP2D terdiri dari beberapa tahapan: identifikasi potensi dan masalah, perumusan rencana aksi, tindak lanjut (survei, sosialisasi, persiapan sarana dan prasarana, pelatihan budi daya lebah madu), evaluasi dan tindak lanjut program pada Kelompok Rukun Tani. Hasil observasi terhadap program pengembangan masyarakat yang dilakukan oleh PHP2D menunjukkan bahwa kegiatan ini belum sepenuhnya dijalankan dengan semangat pengembangan masyarakat. Kegiatan yang dilakukan cenderung top down dan berupa transfer pengetahuan tanpa ada pengorganisasian subjek pengembangan masyarakat. Aktivitas yang dilakukan menunjukkan tidak adanya partisipasi langsung oleh kelompok Rukun tani sehingga tidak muncul kolektivitas kelompok Rukun tani terhadap program PHP2D Desa Bantarsari dan tidak terlaksananya keberlanjutan program.